Effects of high-resolution esophageal manometry on oxygen saturation and hemodynamic function. Issue 3 (2nd March 2017) - Ortiz, Vicente; Sáez-González, Esteban; Blé, Michel; Díaz-Jaime, Francia Carolina; Vinaixa, Carmen; Garrigues, Vicente
SUMMARY: The effect of high-resolution esophageal manometry (HRM) on oxygen saturation (SaO2 ) and hemodynamic function has not been previously evaluated. This was a prospective study of consecutive patients referred for HRM. Demographic and clinical data were collected on all patients. The study variables included SaO2, heart rate (HR) and blood pressure (BP). SaO2 and HR were measured at baseline, during intubation, during and 5 min after HRM. BP was measured at baseline, during and after HRM. 158 (56% women) patients with a mean age of 56 (SD 15) years were included. Thirty-five (22%) were obese and 55 (35%) were overweight. Eighteen (12%) patients had a history of respiratory disease and 27 (17%) were smokers. Intubation was difficult in 22%. Exploration tolerance was poor in 17% or very poor in 6%. The average duration of the test was 9.9 (SD 2.8) minutes. Sixty-four (47%) and 59 (37%) patients had SaO2 below 95% during intubation and during HRM, respectively. Three patients had SaO2 ≤90%. Sixty-nine (44%) patients had tachycardia during intubation and 8 (5%) during HRM. The appearance of desaturation (SaO2 <95%) during intubation was associated with a lower basal SaO2 ; desaturation during HRM and 5 minutes after HRM was associated with a higher age, a higher BMI and a lower basal SaO2 . HRM decreases SaO2 and increases heart rate primarily during the insertion of the probe, as part of the standard stress response and therefore HMR can be considered a safe procedure. However, in older and overweight patients, respiratory parameters should be monitored.